2012
DOI: 10.1128/jcm.00982-12
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Determinants of Drug-Resistant Tuberculosis among HIV-Infected Patients in Nigeria

Abstract: Total RIF resistance indicative of MDR-TB in treatment-naive patients was 5.52%, far exceeding the World Health Organization predictions (0 to 4.3%). RIF resistance was found in 6/213 (2.8%) cases, INH resistance was found in 3/215 (1.4%) cases, and MDR-TB was found in 8/223 (3.6%) cases. We found significantly different amounts of DR-TB by location (18.18% in the south of the country versus 3.91% in the north central region [P < 0.01]). Furthermore, RIF resistance was genetically distinct, suggesting possible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
21
5
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 27 publications
6
21
5
1
Order By: Relevance
“…In addition, studies from different geographic zones have showed varied prevalence of RIF resistance which all differ from the prevalence obtained from this present study as reported by Akaninyene and Dinic [23,24]. Also, comparatively a study done in Nnewi, South East Nigeria shared a similar view (prevalence of RIF's resistance of 2.7%) with this present study, although the general MDR-TB from their study was lesser (7.7%) than that obtained here (10.3%) Uzoewulu though, RIF resistance had the least prevalence when compared to isoniazid thus, it could be deduced that the non-resistant RIF strain might be isoniazid resistant strain and resistant to other TB drugs.…”
Section: Discussioncontrasting
confidence: 99%
“…In addition, studies from different geographic zones have showed varied prevalence of RIF resistance which all differ from the prevalence obtained from this present study as reported by Akaninyene and Dinic [23,24]. Also, comparatively a study done in Nnewi, South East Nigeria shared a similar view (prevalence of RIF's resistance of 2.7%) with this present study, although the general MDR-TB from their study was lesser (7.7%) than that obtained here (10.3%) Uzoewulu though, RIF resistance had the least prevalence when compared to isoniazid thus, it could be deduced that the non-resistant RIF strain might be isoniazid resistant strain and resistant to other TB drugs.…”
Section: Discussioncontrasting
confidence: 99%
“…However, it was lower compared to reports in Nigeria (31.4%) [18] and Pakistan (37%) [19]. The lower proportion rate of confirmed M. tuberculosis in the present study compared to other studies is due to the fact that we included presumptive cases to identify M. tuberculosis while other studies included identified cases of M. tuberculosis to check gene Xpert technique.…”
Section: Discussioncontrasting
confidence: 83%
“…Therefore Xpert® MTB/RIF assay was used in detecting Rifampicin resistance. Rifampicin resistance of 6.6% found in this study is very close to the 7.0% reported in samples collected from Jos and Lagos, Nigeria [11]. Another study in Calabar Nigeria reported a rifampicin resistance of 6%, although they did not find any patient with resistance to only rifampicin [12].…”
Section: Discussionsupporting
confidence: 79%